Predictive value of plasma cytokines for acute kidney injury following lung resection surgery: prospective observational study - Monteserín Matesanz,Cristina (2019)
Abstract Background and objectives: Patients undergoing lung resection surgery are at risk of developing postoperative acute kidney injury. Determination of cytokine levels allows the detection of an early inflammatory response. We investigated any temporal relationship among perioperative inflammatory status and development of acute kidney injury after lung resection surgery. Furthermore, we evaluated the impact of acute kidney injury on outcome and analyzed the feasibility of cytokines to predict acute kidney injury. Methods: We prospectively analyzed 174 patients scheduled for elective lung resection surgery with intra-operative periods of one-lung ventilation periods. Fiberoptic broncho-alveolar lavage was performed in each lung before and after one-lung ventilation periods for cytokine analysis. As well, cytokine levels were measured from arterial blood samples at five time points. acute kidney injury was diagnosed within 48 h of surgery based on acute kidney injury criteria. We analyzed the association between acute kidney injury and cardiopulmonary complications, length of intensive care unit and hospital stays, intensive care unit re-admission, and short-term and long-term mortality. Results: The incidence of acute kidney injury in our study was 6.9% (12/174). Acute kidney injury patients showed higher plasma cytokine levels after surgery but differences in alveolar cytokines were not detected. Although no patient required renal replacement therapy, acute kidney injury patients had higher incidence of cardiopulmonary complications and increased overall mortality. Plasma interleukin-6 at 6 h was the most predictive cytokine of acute kidney injury (cut-off point at 4.89 pg.mL-1). Conclusions: Increased postoperative plasma cytokine levels are associated with acute kidney injury after lung resection surgery in our study, which worsens the prognosis. Plasma interleukin-6 may be used as an early indicator for patients at risk of developing acute kidney injury after lung resection surgery.